Effects of (in)alienability on the expression of possessive relations in the language of Plautus’ plays - Gnjatović, Tena (2010)
The aim of this paper is to analyse possessive constructions in the language of Plautus’ plays and see whether there is any difference in expressing alienable and what may be perceived as inalienable relations. Since nouns denoting kinship and body parts make up the two most frequent semantic groups treated as inalienable in languages in which the distinction between alienable and inalienable possession is grammaticalized, a corpus of twelve plays was searched based on a list of possibly inalienable nouns including body part terms and kin terms. Certain partitive relations were subsequently included in the analysis. To see whether these putatively inalienable nouns appear in different possessive constructions than alienable ones, the prologues and the first two acts of each of the twelve plays were searched for instances of alienable nouns occurring in possessive constructions, which were then compared to the first group. The general finding is that, although the distinction between alienable and inalienable possession is not grammaticalized in Early Latin, i.e. there is no alienability split which requires different possessive constructions for alienables as opposed to inalienables, it seems to have been more appropriate to use certain constructions, such as the possessive adjective or possessor promotion and deletion, with inalienable nouns than with alienable ones. The result is a higher frequency of these constructions in cases when the possessed noun tends to be perceived as inalienable from the possessor.
Projekt MZOS
ENG